2018
DOI: 10.4014/jmb.1710.10021
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Approach to Identifying Foodborne Pathogens on Chinese Cabbage

Abstract: Foodborne illness represents a major threat to public health and is frequently attributed to pathogenic microorganisms on fresh produce. Recurrent outbreaks often come from vegetables that are grown close to or within the ground. Therefore, the first step to understanding the public health risk of microorganisms on fresh vegetables is to identify and describe microbial communities. We investigated the phyllospheres on Chinese cabbage ( subsp. , = 54). 16S rRNA gene amplicon sequencing targeting the V5-V6 regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 54 publications
3
11
2
1
Order By: Relevance
“…In this regard, metagenomic analysis based on 16S rRNA gene fragments is frequently used as a rapid and reliable method to study biodiversity and population dynamics in fermented foods (Kim et al . ; Naik et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, metagenomic analysis based on 16S rRNA gene fragments is frequently used as a rapid and reliable method to study biodiversity and population dynamics in fermented foods (Kim et al . ; Naik et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…pekinensis) as main ingredient. In this context, we would like to propose that the origin of the KM1 stain is most probably the Baechu cabbage itself as P. agglomerans was shown to grow as an epiphyte on vegetables and fruits [68,69]. However, one cannot exclude contamination of kimchi by humans during the preparation process, as P. agglomerans was found in sputum of cystic fibrosis patient.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Sphingomonas generally acts as a plant-protective genus by suppressing disease symptoms and decreasing pathogen growth ( Kim D. et al, 2018 ). Innerebner et al (2011) showed that the inoculation with a Sphingomonas sp.…”
Section: Discussionmentioning
confidence: 99%